Ordered Mesoporous Carbons And Its Alginate Composite Adsorbents: Syntheses, Characterizations And Adsorption Performances For Methylene Blue, Chloramphenicol And Riboflavin - Mohd Din, Azam Taufik (2014)
Ordered mesoporous carbons (OMC) were synthesized through nanocasting method by using lab-synthesized hexagonal mesoporous silica (HMS) as a template and polyethylene glycol 400 (PEG-400) as a carbon source. One-time variable experimental approach was deployed to study the effect of selected process parameters including carbonization temperature (873-1073 K), dwelling time (15-240 min), heating rate (1-10 K.min-1) and PEG-400 (2.5-15 g) loading on the surface area properties, yields and its ability to remove methylene blue (MB). Karbon mesoliang tersusun (KMT) telah disintesis menerusi kaedah tempa nano menggunakan silika mesoliang heksagonal (SMH) sebagai templat dan polietilena glikol 400 (PEG-400) sebagai sumber karbon. Pendekatan eksperimen pemboleh ubah satu-masa telah digunakan untuk mengkaji kesan parameter proses terpilih termasuk suhu pengkarbonan (873-1073 K), masa penahanan (15-240 min), kadar pemanasan (1-10 K.min-1) dan muatan PEG-400 (2.5-15 g) ke atas sifat-sifat luas permukaan, hasil dan kebolehan untuk menyingkirkan metilena biru (MB).